The Indian Dimension of Aceh and Sumatra History - Anthony Reid (Diponegoro University, 2020)
Indonesia’s maritime boundary with India, lying barely 100km from Banda Aceh, appears quiet and of little interest to policy-makers, in contrast to almost all the other contested boundaries with Malaysia, China, the Philippines, and Australia. India’s historical relations with Sumatra have also drawn less scholarly or popular attention than those with the Arab, Persian, and Turkish worlds, or with Java, the Peninsula, and China. It is one of the imbalances and justifying the “Indian Ocean’ in the title of International Centre for Aceh and Indian Ocean Studies. It is also supported by arguing that northern Sumatra’s most important historical relationship outside Sumatra itself was for long with India. The time must come when this neighbourly maritime relationship is normalised in the context of improving Indonesia-India ties.